(untitled) (Journal of Pathology of Nepal, 2018)
Gastroduodenal tuberculosis is uncommon even in parts of world where tuberculosis is endemic and accounts for 2.3 % of abdominal tuberculosis. We present here a case of duodenal tuberculosis who presented with vomiting, pain abdomen and weight loss. Duodenoscopy revealed mucosal ulceration and nodularity with marked enlarged and erythematous surrounding folds. Histopathology of duodenum showed features of tuberculosis.